The Maine Shore and the Army Corps: A Tale of Two Harbors, Wells and Saco, Maine - Kelley, Joseph; Anderson, Walter (Maine Policy Review, 2000)
By discussing the problems of beach erosion and sand movement at Wells and Saco, Maine, Joseph Kelley and Walter Anderson demonstrate how single-minded, engineering approaches to complex, interdisciplinary coastal issues can create bigger problems than previously existed. As Kelley and Anderson explain, at both Wells and Camp Ellis, the Army Corps of Engineers was brought in to construct a harbor at no local cost to the community. This was accomplished by constructing jetties, and the result has been a persistent and serious problem of beach erosion. Over the years, the Army Corps has offered further technical solutions that have served only to exacerbate the problem. In pointing out the shortcomings of these solutions, Kelley and Anderson call for new action requiring federal, state, and local involvement. To do nothing, they argue, is to absorb the costs of letting nature run its course.